RADIOSURGICAL TREATMENT OF BENIGN SMALL EYELID TUMORS - S. V. Saakyan; M. P. Kharlampidi; E. B. Myakoshina; R. A. Tatskov; G. A. Gusev (Сибирский научный медицинский журнал)
Aim of the study – to evaluate the long-term results of the radiosurgical method using microsurgical techniques for the treatment of small benign eyelid tumors. Material and methods. In Ocular Oncology Centre of Helmholtz Moscow Research Institute of Eye Diseases for the period from 2012 to 2018 year 248 patients were examined and treated (108 children aged 12 ± 1.2 years and 140 adults aged 46 ± 8.1 years) with benign eyelid tumors: pigmented (nevus), vascular (capillary hemangiomas), epithelial (follicular keratosis, keratopapilloma). The Surgitron EMC radiosurgery device was used as surgical aids. All patients used microsurgical technique. The longitudinal size of the tumors was 3.4 ± 0.5 mm, transverse – 6 ± 0.8 mm. All patients after surgical treatment underwent histopathological study. The observation period is on average 6 ± 1.4 years. Results. In 133 (53.6 %) of 248 patients, nevi were detected, in 76 (30.7 %) – keratopapilloma and inverted follicular keratosis, in 39 (15.7 %) – capillary hemangioma. Various modifications of radiosurgical treatment were used depending on the location of the tumor, its size, the degree of activity using different modes and powers from 1 to 4 Wt. Intraoperative complications were not noted. The early postoperative period was accompanied by the presence of signs of mild inflammation, which was stopped by local therapy. The formation of a tender scar was observed on average after 7 ± 2 days. Two cases (0.8 %) of recurrence of keratopapilloma were noted 2 years after the first operation. Tumors were removed by radio excision. Conclusion. Benign eyelid tumors, especially of melanocytic origin, are subject to obligatory dynamic observation, and if minimal signs of their progression are detected, their surgical removal is indicated. Radiosurgical treatment using microsurgical techniques is the method of choice in the treatment of small benign eyelid tumors and depends on the size of the tumor, its localization and the nature of the tumor process. The use of the radiosurgical method with obligatory microsurgical technique for treating benign tumors of small sizes with the observance of the rules of radicalness and antiblasticity allows maintaining visual functions with simultaneous surgical treatment, providing normal anatomical and topographic correlations of the anterior segment of the eye and high quality of life of the patient.